Variable effects of transient Wolbachia infections on alphaviruses in Aedes aegypti. - Brittany L Dodson; Sujit Pujhari; Marco Brustolin; Hillery C Metz; Jason L Rasgon (PLoS Neglected Tropical Diseases)
Wolbachia pipientis (= Wolbachia) has promise as a tool to suppress virus transmission by Aedes aegypti mosquitoes. However, Wolbachia can have variable effects on mosquito-borne viruses. This variation remains poorly characterized, yet the multimodal effects of Wolbachia on diverse pathogens could have important implications for public health. Here, we examine the effects of transient somatic infection with two strains of Wolbachia (wAlbB and wMel) on the alphaviruses Sindbis virus (SINV), O'nyong-nyong virus (ONNV), and Mayaro virus (MAYV) in Ae. aegypti. We found variable effects of Wolbachia including enhancement and suppression of viral infections, with some effects depending on Wolbachia strain. Both wAlbB- and wMel-infected mosquitoes showed enhancement of SINV infection rates one week post-infection, with wAlbB-infected mosquitoes also having higher viral titers than controls. Infection rates with ONNV were low across all treatments and no significant effects of Wolbachia were observed. The effects of Wolbachia on MAYV infections were strikingly strain-specific; wMel strongly blocked MAYV infections and suppressed viral titers, while wAlbB had more modest effects. The variable effects of Wolbachia on vector competence underscore the importance of further research into how this bacterium impacts the virome of wild mosquitoes including the emergent human pathogens they transmit.